Qualitative analysis of emerging housing: Case study Fractionation "Nuevo Mirador" Chilpancingo, Guerrero. - Adame-Arcos, Daniela; Ascencio-Lopez, Osvaldo (Pädi Boletín Científico de Ciencias Básicas e Ingenierías del ICBI, 2021)
In September 2013, storm “Manuel” and hurricane “Ingrid” devastated much of the state of Guerrero, Mexico, as a result of the surgical procedure of a large number of victims throughout the state territory. The authorities generated different housing solutions, including the “Nuevo Mirador” subdivision in the city of Chilpancingo. The present work gives an approach to the concept of "emergent housing" and studies this subdivision with the application of the analysis of the basic building design in the elaboration of a field logbook with a qualitative approach, analyze the eventual modelers that require the occupant’s requirements, determinants of the natural and artificial context with the complement of the formal attributes of the fractionation resulting in the features of the complication in the resolving conflict, allowing a complete analysis of the object of study